P319 Long-term outcomes after anti-TNF therapy withdrawal in patients with radiologically healed perianal Crohn's fistulas. (16th January 2018) - Mak, W Y; Adegbola, S; Sahnan, K; Tozer, P; Lung, P; Hart, A; Ng, S C
Abstract: Background: In patients with perianal Crohn's fistulas (pCF), we showed that radiological healing lags behind clinical healing by 12 month. 1 Whether anti-TNF therapy can be stopped in patients with pCF who achieved radiological healing is unclear. We evaluated long-term outcomes of subjects with pCF who achieved complete radiological healing on magnetic resonance imaging (MRI). Methods: Retrospective review of consecutive pCF patients diagnosed between 2001 and 2015 recruited from two sites: St. Marks Hospital, London and the Hong Kong IBD Registry. Radiological healing was defined as complete resolution of previous high signal tract or a subtle, narrow calibre intermediate signal residual tract . Results: Amongst 339 subjects with pCF, we have identified 26 patients who have achieved radiological healing from year 2008 to 2016. Median age at diagnosis of pCF was 26 years (IQR: 20–32 years) and median follow-up was 101 months (IQR: 62–138 months). Eighteen were White, six were Chinese, and two were of Indian origin. Eleven had proctitis at diagnosis of pCF. All received anti-TNF prior to radiological healing. Median duration from diagnosis to radiological healing was 53 months (IQR: 23–83 months). Sixteen patients continued anti-TNF following radiological healing. None of these patients developed fistula recurrence following radiological healing. Maintenance anti-TNF therapy was significantly associated with absence of pCF recurrence ( p < 0.05). Ten patients stopped maintenance biologic therapy following radiological healing. All had good control of luminal disease at the time of stopping anti-TNF therapy. Six of the patients who stopped anti-TNF had fistula recurrence after achieving radiological healing of their fistula, and five of these were subsequently recommenced on anti-TNF therapy. Median time to pCF recurrence after MRI healing was 21 months (IQR, 12–54 months). Conclusions: Radiological healing does not necessarily warrant cessation of biologic therapy. Sixty percent of patients with pCF who stopped anti-TNF therapy went on to develop fistula recurrence. Maintenance therapy with anti-TNF was associated with maintained healing of pCF. References: 1. Tozer P, Ng SC, Siddiqui MR, et al . Long-term MRI-guided combined anti-TNF-α and thiopurine therapy for Crohn's perianal fistulas. Inflamm Bowel Dis, 2012;18:1825–34.